INTEGRATING BIOREACTOR SYSTEM TO SPEED UP TUMOUR INFILTRATING LYMPHOCYTES (TILS) IMMUNOTHERAPY COMMERCIALIZATION - BUDIYATI, A. D.; PAWITAN, J. A. (International Journal of Applied Pharmaceutics, 2020)
One of the major breakthroughs on adoptive cell transfer (ACT) is autologous T cells transfer that either derived from tumour infiltrating lymphocytes (TILs) or genetically engineered T cells, which express tumour recognizing receptors. Between those two, when the purpose is to treat solid tumours, a more impressive clinical trial result is demonstrated by TIL therapy. The efficacy of TIL therapy is due to its highly personalized approach in generating T cells from the patient’s own tumour tissue. Regardless to its efficacy, TIL therapy in a commercial setting is limited, mainly due to the complexity and costs of cell expansion protocols. This issue has triggered the need to develop effective methods to expand TILs ex vivo, in a safe, efficient, and reproducible manner. In line with this need, there are two main types of bioreactors that have recently been used to generate T cells for ACT, which might suit the requirements for TIL manufacture. Therefore, in this review, we highlighted recent updates on TILs expansion protocol, particularly in autologous settings, as well as the aspect of each bioreactor to be considered before integrating them into TIL manufacturing process.